Fungi inhabiting attine ant colonies: reassessment of the genus Escovopsis and description of Luteomyces and Sympodiorosea gens. nov. - Quimi Vidaurre Montoya; Maria Jesus Sutta Martiarena; Rodolfo Bizarria Jr.; Nicole Marie Gerardo; Andre Rodrigues (IMA Fungus)
Abstract Escovopsis is a diverse group of fungi, which are considered specialized parasites of the fungal cultivars of fungus-growing ants. The lack of a suitable taxonomic framework and phylogenetic inconsistencies have long hampered Escovopsis research. The aim of this study is to reassess the genus Escovopsis using a taxonomic approach and a comprehensive multilocus phylogenetic analysis, in order to set the basis of the genus systematics and the stage for future Escovopsis research. Our results support the separation of Escovopsis into three distinct genera. In light of this, we redefine Escovopsis as a monophyletic clade whose main feature is to form terminal vesicles on conidiophores. Consequently, E. kreiselii and E. trichodermoides were recombined into two new genera, Sympodiorosea and Luteomyces, as S. kreiselii and L. trichodermoides, respectively. This study expands our understanding of the systematics of Escovopsis and related genera, thereby facilitating future research on the evolutionary history, taxonomic diversity, and ecological roles of these inhabitants of the attine ant colonies.